I am trying to solve this PDE using method of characteristics:

$u_y + 3u_x = -u^2, u(x,0)=f(x)$

This is how I started:




I then integrated these equations and got:




Next step, find $s$ and $u_0$. I let $y_0=0$ so $s=y$. To get my $u_0$:




Finally, I put $s$ and $u_0$ in my expression for $u$ to get the solution:


But that isn't the same solution as the one my professor got. I don't understand what I did wrong. Is there something wrong with my use of the initial condition?


1 Answer 1


Obviously, the solution that you got $\quad u(x,y)=\frac{1}{y+f(x-3y)}\quad$ doesn't fit the specified boundary condition :

$u(x,0)=\frac{1}{0+f(x-3(0))}=\frac{1}{f(x)}$ which is not $u(x,0)=f(x)$ as expected.

In fact, you found the general solution : $$\quad u(x,y)=\frac{1}{y+F(x-3y)}$$ where $F$ is an arbitrary function.

Don't confuse $F$ with $f$.

Then, the condition is :

$u(x,0)=\frac{1}{0+F(x-3(0))}=\frac{1}{F(x)}=f(x)\quad$ which determines the function $F(X)=\frac{1}{f(X)}$

Putting it into the general solution where $X=x-3y$ and $F(x-3y)=\frac{1}{f(x-3y)}$leads to the particular solution which fits the condition.

$u(x,y)=\frac{1}{y+F(x-3y)}=\frac{1}{y+\frac{1}{f(x-3y)}}$ $$u(x,y)=\frac{f(x-3y)}{y\;f(x-3y)+1}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.